Random Mutagenesis Applied to Reveal Factors Involved in Oxidative Tolerance and Biofilm Formation in Foodborne Cronobacter malonaticus - Zhang, Maofeng; Zhang, Xiyan; Tong, Liaowang; Ou, Dexin; Wang, Yaping; Zhang, Jumei; Wu, Qingping; Ye, Yingwang (Frontiers in Microbiology, 2019)
Cronobacter species are linked with life-treating diseases in neonates and show strong tolerances to environmental stress. However, the information about factors involved in oxidative tolerance in Cronobacter remains elusive. Here, factors involved in oxidative tolerance in C. malonaticus were identified using a transposon mutagenesis. Eight mutants were successfully screened based on a comparison of the growth of strains from mutant library (n = 215) and wild type (WT) strain under 1.0 mM H2O2. Mutating sites including thioredoxin 2, glutaredoxin 3, pantothenate kinase, serine/threonine protein kinase, pyruvate kinase, phospholipase A, ferrous iron transport protein A, and alanine racemase 2 were successfully identified by arbitrary PCR and sequencing alignment. Furthermore, the comparison about quantity and structure of biofilms formation among eight mutants and WT was determined using crystal violet staining (CVS), scanning electron microscopy (SEM), and confocal laser scanning microscopy (CLSM). Results showed that the biofilms of eight mutants significantly decreased within 48 h compared to that of WT, suggesting that mutating genes play important roles in biofilm formation under oxidative stress. The findings provide valuable information for deeply understanding molecular mechanism about oxidative tolerance of C. malonaticus.